The Workers' Festival : A History of Labour Day in Canada - Heron, Craig (Book collections on Project MUSE., 2005)
The Workers' Festival ranges widely into many key themes of labour history - union politics and rivalries, radical movements, religion, race and gender, and consumerism/leisure - as well as cultural history - public celebration/urban procession, urban space and communication, and popular culture.